Report of the Family Planning Third Five Year Plan Committee 1960 - Ministry of Health, Government of India (Ministry of Health, Government of India, 1960)
Appointment of the Committee The Central Family Planning Board at its meeting on the 31st August, 1959 recommended that a Family Planning Third Five Year Plan Committee should be formed with Shrimati Dhanvanthi Rama Rau as Chairman, Dr. Shrimati Soundaram Ramachandaran, Shrimati Shakuntala Paranjpye., Dr. Shrimati Kamala Rainier, and Dr Shrimati H. N. Unwallaas members and Lieut.-Colonel B.L. Raina, as Member-Secretary. The Ministry of Health constituted the present Committee under the Government of India, Ministry of Health letter No. F. 4-38/59-F.P., dated the 29th September, 1959. (See Appendix I).
Ministry of Health Government of India
Ministry of Health, Government of India